High-temperature co-fired multilayer ceramic substrate and preparation method thereof
By introducing specific components into the high-temperature co-fired multi-layer ceramic substrate to form a dense structure, the problem of poor flexural strength is solved, higher flexural strength and wear resistance are achieved, and yield and reliability are improved.
Patent Information
- Application Number
- CN202510385495.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-29
AI Technical Summary
Due to the high-temperature co-fired multi-layer ceramic substrate, the material selection is limited, resulting in poor flexural strength and reduced yield and reliability.
By introducing alumina, tungsten diboride, borate compounds, sintering aids, dispersants, binders and solvents, a dense multi-layer ceramic substrate structure is formed to improve the bending strength of the ceramic substrate.
The bending strength of the multi-layer ceramic substrate is significantly improved, structural stability is enhanced, wear resistance is improved, and yield and reliability are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic substrates, and in particular to a high-temperature co-fired multi-layer ceramic substrate and a preparation method thereof. Background Art
[0002] Multilayer ceramic substrates are also called ceramic shells. While serving as a medium for signal transmission and heat dissipation, they can also protect packaged devices from various physical and chemical hazards. Due to their excellent thermal conductivity, high rigidity and other properties, they can be widely used in energy, medical care, communications and other fields.
[0003] The manufacturing of multilayer ceramic substrates often uses high-temperature co-firing and low-temperature co-firing ceramic technologies due to the differences in the materials used and the sintering temperatures. Both preparation methods allow each layer in the ceramic substrate to be independently manufactured, tested and replaced, but the high-temperature co-firing ceramic technology is more mature than the low-temperature co-firing ceramic technology. High-temperature co-firing multilayer ceramic substrates are mostly made of alumina, aluminum nitride, beryllium oxide, etc. as ceramic materials, and tungsten, molybdenum, etc. as conductor materials. Multilayer ceramic substrates are prepared at a sintering temperature above 1400°C.
[0004] However, due to the high sintering temperature, the material selection of high-temperature co-fired multilayer ceramic substrates is severely limited. In high-temperature environments, some materials with higher melting points are mainly used. In addition to aluminum oxide and aluminum nitride, there are some other high-temperature resistant materials. Although these materials have high melting points, they are expensive, and there is a problem of poor compatibility of materials under high-temperature sintering, which will affect the bending strength of the ceramic substrate and reduce its yield and reliability.
[0005] Therefore, developing a multilayer ceramic substrate that can improve the bending strength of the multilayer ceramic substrate through a high-temperature co-firing process is of great significance for expanding the application of the multilayer ceramic substrate. Summary of the invention
[0006] The present invention provides a high-temperature co-fired multi-layer ceramic substrate and a preparation method thereof, which solves the problem of poor bending strength of the multi-layer ceramic substrate in the related art.
[0007] The technical solution of the present invention is as follows: The present invention provides a high-temperature co-fired multi-layer ceramic substrate, the raw materials of which include the following components in parts by weight: 100 parts of aluminum oxide, 4-12 parts of tungsten diboride, 6-18 parts of borate compounds, 3-6 parts of sintering aids, 2-4 parts of dispersants, 5-10 parts of binders, and 50-60 parts of solvents; The borate compounds include metaborate and polyborate in a weight ratio of 1 to 9:1.
[0008] As a further technical solution, the weight ratio of the metaborate to the polyborate is 3~7:1.
[0009] As a further technical solution, the metaborate includes one or more of sodium metaborate, calcium metaborate, and potassium metaborate; The polyborate includes one of sodium tetraborate and potassium pentaborate.
[0010] As a further technical solution, the raw material further includes the following components in parts by weight: 2 to 8 parts of crystalline silicon dioxide.
[0011] In the present invention, crystalline silica is introduced into the multilayer ceramic substrate. The crystalline silica can assist the borate compound in adjusting the pore structure of the ceramic substrate. When the ceramic substrate is subjected to external force, the crystalline silica and other components can hinder the internal dislocation movement of the ceramic substrate, so that the surface of the ceramic substrate is not prone to wear marks when subjected to friction, thereby improving the wear resistance of the ceramic substrate.
[0012] As a further technical solution, the crystalline silica is titanium composite crystalline silica.
[0013] As a further technical solution, the raw materials of the titanium composite crystalline silica include crystalline silica and a titanium source in a weight ratio of 16:1 to 5; The titanium source includes one of titanium acetylacetonate and titanium citrate, preferably titanium acetylacetonate.
[0014] In the present invention, acetylacetonato titanium or titanium citrate is used as a titanium source to perform a composite treatment on crystalline silica, and the weight ratio of crystalline silica to the titanium source is adjusted to be 16:1-5, which can further improve the wear resistance of the ceramic substrate. The reasons may be speculated as follows: in the early stage of preparing the casting slurry, acetylacetonato titanium or titanium citrate is used as a titanium source to perform a composite treatment on crystalline silica, which can further improve the uniformity of crystalline silica in the casting slurry, so that the formed raw ceramic sheet has a uniform and stable internal structure; in the later stage, a dense film structure can be formed on the surface of the crystalline silica through sintering treatment, thereby further improving the wear resistance of the ceramic substrate.
[0015] As a further technical solution, the preparation method of the titanium composite crystalline silica comprises the following steps: A1, adding the crystalline silica to an alkaline solution, dispersing evenly, concentrating, and drying to obtain pretreated crystalline silica; A2. Dissolve the titanium source in isopropanol, add the pretreated crystalline silica, disperse, concentrate, dry, and calcine to obtain titanium composite crystalline silica.
[0016] As a further technical solution, the weight ratio of the crystalline silica to the titanium source is 16:2~3.
[0017] When the weight ratio of crystalline silica to titanium source is 16:2-3, the wear resistance of the ceramic substrate is better, and the wear rate of the ceramic substrate can be reduced to 2.76×10 -6 ~2.82×10 -6 mm 3 / mN, and when the weight ratio of crystalline silica to titanium source is outside the range of 16:2~3, the wear resistance of the ceramic substrate is not as good as that when the weight ratio of crystalline silica to titanium source is 16:2~3.
[0018] As a further technical solution, in step A1, the alkaline solution is one of sodium hydroxide solution, sodium carbonate solution, and sodium bicarbonate solution, and the mass fraction of the alkaline solution is 1% to 3%.
[0019] As a further technical solution, in step A1, the weight ratio of the crystalline silica to the alkaline solution is 1:1~1.06.
[0020] As a further technical solution, in step A1, the dispersion time is 10 to 18 minutes.
[0021] As a further technical solution, in step A2, the calcination temperature is 500-600° C. and the calcination time is 1-2 hours.
[0022] The sintering aid in the present invention can be any one or more conventional sintering aids in the art, for example, it can be one or more of Y2O3, Li2O, Cr2O3, La2O3, preferably Y2O3, Cr2O3, La2O3 in a weight ratio of 2:1:1. In the later stage of sintering, the ceramic material is prone to abnormal grain growth, which affects the densification of the internal structure of the ceramic substrate. By adding the sintering aid, the grains can grow more uniformly, and the sintering temperature range of each component in the ceramic substrate can be appropriately expanded, making the ceramic substrate easier to form.
[0023] The dispersant in the present invention can be any one or more conventional dispersants in the art, for example, one or both of tributyl phosphate and triolein, preferably triolein. By adding the dispersant, the casting slurry can be evenly dispersed, the agglomeration and sedimentation of ceramic powder can be reduced, and the stability of the green ceramic sheet can be improved.
[0024] The binder in the present invention can be any one or more conventional binders in the art, for example, it can be one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, polyvinyl butyral, preferably hydroxypropyl methyl cellulose. After the binder is added to the casting slurry, it can be dispersed between the components during the casting process, and when the solvent evaporates, its own solidification and bonding effect can play a bridging role on the ceramic powder material, and under the action of the binder and the components, the bending strength of the ceramic substrate is improved.
[0025] The solvent in the present invention can be any one or more conventional solvents in the art, for example, water and an organic solvent in a weight ratio of 3 to 4:1, wherein the organic solvent can be one or more of ethanol, n-butanol, and acetone, preferably ethanol.
[0026] The present invention also provides a method for preparing a high-temperature co-fired multi-layer ceramic substrate, which is used to prepare the high-temperature co-fired multi-layer ceramic substrate, comprising the following steps: S1, after mixing the remaining raw materials except the solvent, dispersant and binder, adding the solvent and dispersant, performing the first ball milling, adding the binder, performing the second ball milling, and obtaining the casting slurry; S2, degassing, casting and drying the tape-casting slurry to obtain a green porcelain tape; S3, punching, filling, printing, laminating, sintering and cooling the raw ceramic tape to obtain a high-temperature co-fired multi-layer ceramic substrate.
[0027] As a further technical solution, in step S1, during the first ball milling, the speed is 300-400 rpm, and the time is 1.5-2.5 h; during the second ball milling, the speed is 400-500 rpm, and the time is 1-2 h.
[0028] As a further technical solution, in step S3, the punching pressure is 0.5-0.7 MPa.
[0029] As a further technical solution, in step S3, the printed material is tungsten paste, and the printing thickness of the tungsten paste is 15-20 μm.
[0030] As a further technical solution, in step S3, when stacking, the number of layers is 35-40.
[0031] As a further technical solution, in step S3, during the sintering, the temperature is 1420-1550° C., the time is 30-50 min, and the sintering atmosphere is air.
[0032] The working principle and beneficial effects of the present invention are: 1. In the present invention, alumina is the main material of the multilayer ceramic substrate, which gives the multilayer ceramic substrate basic strength and stability. After the joint action of tungsten diboride, borate compounds, sintering aids, dispersants, binders and solvents, a multilayer ceramic substrate with good density and excellent bending strength is formed in the subsequent processing process; among them, tungsten diboride itself has a high hardness, and adding it to the multilayer ceramic substrate can reduce the surface damage of the multilayer ceramic substrate during assembly and use. At the same time, it works together with alumina to make the multilayer ceramic substrate have good heat dissipation capacity.
[0033] 2. In the present invention, the borate compounds include metaborate and polyborate. By introducing two different borate compounds into the multilayer ceramic substrate and adjusting the weight ratio of metaborate to polyborate to be 1-9:1, the internal stress caused by solvent volatilization can be reduced during the sintering process, and the density of the internal structure of the ceramic substrate is improved, thereby improving the bending strength of the multilayer ceramic substrate and enhancing the structural stability of the entire ceramic material. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In the following embodiments and comparative examples, the average particle size of aluminum oxide is 10 μm; the average particle size of tungsten diboride is 5 μm; the effective ingredient content of sodium metaborate is 99.0%; sodium tetraborate is anhydrous sodium tetraborate, and the effective ingredient content is 99.5%; the viscosity of hydroxypropyl methylcellulose is 150,000 mPa·s; the crystalline silicon dioxide, specifically quartz sand, has an average particle size of 25 μm; the amorphous silicon dioxide, specifically diatomaceous earth, has an average particle size of 25 μm.
[0036] Example 1 A high-temperature co-fired multi-layer ceramic substrate, the raw materials include the following components in parts by weight: 100 parts of aluminum oxide, 4 parts of tungsten diboride, 6 parts of borate compounds, 1.5 parts of Y2O3, 0.75 parts of Cr2O3, 0.75 parts of La2O3, 2 parts of triolein, 5 parts of hydroxypropyl methylcellulose, 37.5 parts of water, 12.5 parts of ethanol; The borate compound includes 3 parts of sodium metaborate and 3 parts of sodium tetraborate; A method for preparing a high-temperature co-fired multilayer ceramic substrate comprises the following steps: S1. After mixing alumina, tungsten diboride, borate compounds, Y2O3, Cr2O3 and La2O3, water, ethanol and triolein were added, and the mixture was ball-milled at 300 rpm for 2.5 h. Hydroxypropyl methylcellulose was added, and the mixture was ball-milled at 400 rpm for 2 h to obtain a casting slurry. S2, degassing, casting and drying the tape-casting slurry to obtain a green porcelain tape; S3. Punch holes in the green porcelain tape at 0.5 MPa, fill the holes, print tungsten paste material with a thickness of 15 μm, stack 35 layers of green porcelain tape, laminate, sinter at 1420° C. in an air atmosphere for 50 minutes, and cool to obtain a multilayer ceramic substrate.
[0037] Example 2 A high-temperature co-fired multilayer ceramic substrate, the raw materials include the following components in parts by weight: 100 parts of aluminum oxide, 8 parts of tungsten diboride, 16 parts of borate compounds, 2.5 parts of Y2O3, 1.25 parts of Cr2O3, 1.25 parts of La2O3, 3 parts of triolein, 8 parts of hydroxypropyl methylcellulose, 42 parts of water, 14 parts of ethanol; The borate compound includes 10 parts of sodium metaborate and 6 parts of sodium tetraborate; A method for preparing a high-temperature co-fired multilayer ceramic substrate comprises the following steps: S1. After mixing alumina, tungsten diboride, borate compounds, Y2O3, Cr2O3 and La2O3, water, ethanol and triolein were added, and the mixture was ball-milled at 350 rpm for 2 h. Hydroxypropyl methylcellulose was added, and the mixture was ball-milled at 450 rpm for 1.5 h to obtain a casting slurry. S2, degassing, casting and drying the tape-casting slurry to obtain a green porcelain tape; S3. Punch holes in the green porcelain tape at 0.7 MPa, fill the holes, print tungsten paste material with a thickness of 20 μm, stack 40 layers of the green porcelain tape, laminate, sinter at 1500° C. in an air atmosphere for 40 minutes, and cool to obtain a multilayer ceramic substrate.
[0038] Example 3 A high-temperature co-fired multilayer ceramic substrate, the raw materials include the following components in parts by weight: 100 parts of aluminum oxide, 12 parts of tungsten diboride, 18 parts of borate compounds, 3 parts of Y2O3, 1.5 parts of Cr2O3, 1.5 parts of La2O3, 4 parts of triolein, 10 parts of hydroxypropyl methylcellulose, 48 parts of water, 12 parts of ethanol; The borate compound includes 16.2 parts of calcium metaborate and 1.8 parts of potassium pentaborate; A method for preparing a high-temperature co-fired multilayer ceramic substrate comprises the following steps: S1. After mixing alumina, tungsten diboride, borate compounds, Y2O3, Cr2O3 and La2O3, water, ethanol and triolein were added, and the mixture was ball-milled at 400 rpm for 1.5 h. Hydroxypropyl methylcellulose was added, and the mixture was ball-milled at 500 rpm for 1 h to obtain a casting slurry. S2, degassing, casting and drying the tape-casting slurry to obtain a green porcelain tape; S3. Punch holes in the green porcelain tape at 0.7 MPa, fill the holes, print tungsten paste material with a thickness of 20 μm, stack 40 layers of the green porcelain tape, laminate, sinter at 1550° C. in an air atmosphere for 30 minutes, and cool to obtain a multilayer ceramic substrate.
[0039] Example 4 The only difference between this embodiment and embodiment 2 is that in this embodiment, the borate compound includes 14.3 parts of sodium metaborate and 1.7 parts of sodium tetraborate.
[0040] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, the borate compound includes 12 parts of sodium metaborate and 4 parts of sodium tetraborate.
[0041] Example 6 The only difference between this embodiment and embodiment 2 is that in this embodiment, the borate compound includes 14 parts of sodium metaborate and 2 parts of sodium tetraborate.
[0042] Example 7 A high-temperature co-fired multilayer ceramic substrate, the raw materials include the following components in parts by weight: 100 parts of aluminum oxide, 8 parts of tungsten diboride, 16 parts of borate compounds, 2 parts of crystalline silicon dioxide, 2.5 parts of Y2O3, 1.25 parts of Cr2O3, 1.25 parts of La2O3, 3 parts of triolein, 8 parts of hydroxypropyl methylcellulose, 42 parts of water, and 14 parts of ethanol; The borate compound includes 14 parts of sodium metaborate and 2 parts of sodium tetraborate; A method for preparing a high-temperature co-fired multilayer ceramic substrate comprises the following steps: S1. Alumina, tungsten diboride, borate compounds, crystalline silica, Y2O3, Cr2O3 and La2O3 were mixed, water, ethanol and triolein were added, and the mixture was ball-milled at 350 rpm for 2 h. Hydroxypropyl methylcellulose was added, and the mixture was ball-milled at 450 rpm for 1.5 h to obtain a casting slurry. S2, degassing, casting and drying the tape-casting slurry to obtain a green porcelain tape; S3. Punch holes in the green porcelain tape at 0.7 MPa, fill holes, print tungsten paste material with a thickness of 20 μm, stack 40 layers of green porcelain tape, laminate, sinter at 1500° C. in air atmosphere for 40 minutes, and cool to obtain a multilayer ceramic substrate.
[0043] Example 8 The only difference between this example and Example 7 is that in this example, 2 parts of crystalline silica are replaced by 8 parts of crystalline silica.
[0044] Example 9 A high-temperature co-fired multi-layer ceramic substrate, the raw materials include the following components in parts by weight: 100 parts of aluminum oxide, 8 parts of tungsten diboride, 16 parts of borate compounds, 8 parts of titanium composite crystalline silica, 2.5 parts of Y2O3, 1.25 parts of Cr2O3, 1.25 parts of La2O3, 3 parts of triolein, 8 parts of hydroxypropyl methylcellulose, 42 parts of water, and 14 parts of ethanol; The borate compound includes 14 parts of sodium metaborate and 2 parts of sodium tetraborate; The preparation method of titanium composite crystalline silica comprises the following steps: A1. Add 16 parts of crystalline silicon dioxide into 16.8 parts of 2% by mass sodium hydroxide solution, disperse for 15 minutes, concentrate, and dry to obtain pretreated crystalline silicon dioxide; A2, dissolving 1 part of titanium acetylacetonate in 20 parts of isopropanol, adding the above-mentioned pretreated crystalline silica, dispersing evenly, concentrating, drying, and calcining at 550° C. for 1.5 h to obtain titanium composite crystalline silica; A method for preparing a high-temperature co-fired multilayer ceramic substrate comprises the following steps: S1. Alumina, tungsten diboride, borate compounds, titanium composite crystalline silica, Y2O3, Cr2O3 and La2O3 were mixed, water, ethanol and triolein were added, and the mixture was ball-milled at 350 rpm for 2 h. Hydroxypropyl methylcellulose was added, and the mixture was ball-milled at 450 rpm for 1.5 h to obtain a casting slurry. S2, degassing, casting and drying the tape-casting slurry to obtain a green porcelain tape; S3. Punch holes in the green porcelain tape at 0.7 MPa, fill holes, print tungsten paste material with a thickness of 20 μm, stack 40 layers of green porcelain tape, laminate, sinter at 1500° C. in air atmosphere for 40 minutes, and cool to obtain a multilayer ceramic substrate.
[0045] Example 10 The difference between this embodiment and embodiment 9 is that in the process of preparing titanium composite crystalline silica in this embodiment, 5 parts of titanium acetylacetonate are added.
[0046] Embodiment 11 The only difference between this embodiment and embodiment 9 is that in the process of preparing titanium composite crystalline silica in this embodiment, 2 parts of titanium acetylacetonate are added.
[0047] Example 12 The only difference between this embodiment and embodiment 9 is that in the process of preparing titanium composite crystalline silica in this embodiment, 3 parts of titanium acetylacetonate are added.
[0048] Embodiment 13 The only difference between this embodiment and embodiment 8 is that in this embodiment, the crystalline silicon dioxide is replaced by an equal amount of amorphous silicon dioxide.
[0049] Comparative Example 1 The only difference between this comparative example and Example 2 is that in this comparative example, sodium tetraborate is replaced by an equal amount of sodium metaborate.
[0050] Comparative Example 2 The only difference between this comparative example and Example 2 is that in this comparative example, sodium metaborate is replaced by an equal amount of sodium tetraborate.
[0051] Comparative Example 3 The only difference between this comparative example and Example 2 is that in this comparative example, no borate compound is added.
[0052] Experimental Example 1 The multilayer ceramic substrates prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were tested for bending strength according to the test method specified in GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics", wherein the test method adopted three-point bending. The test results are shown in Table 1: Table 1 Bending strength test results of Examples 1 to 6 and Comparative Examples 1 to 3
[0053] It can be concluded from Table 1 that, compared with Comparative Examples 1 to 3, the bending strength of the multilayer ceramic substrates prepared in Examples 1 to 6 is improved, indicating that the addition of metaborate and polyborate can improve the bending strength of the multilayer ceramic substrate.
[0054] Experimental Example 2 The multilayer ceramic substrates prepared in Examples 6 to 13 were tested for wear rate of the ceramic substrate samples using a CFT-I type material surface performance comprehensive tester, wherein the test load was 5N. The test results are shown in Table 2: Table 2 Wear rate test results of Examples 6 to 13
[0055] As can be seen from Table 2, compared with Example 6 and Example 13, the wear rate of the multilayer ceramic substrate prepared in Examples 7 to 12 is reduced, indicating that the introduction of crystalline silicon dioxide into the multilayer ceramic substrate can improve the wear resistance of the multilayer ceramic substrate. Compared with Example 8, the wear rate of the multilayer ceramic substrate prepared in Examples 9 to 12 is reduced, indicating that the wear resistance of the multilayer ceramic substrate can be improved by composite treatment of the titanium source and the multilayer silicon dioxide through the subsequent sintering process.
[0056] Experimental Example 3 The multilayer ceramic substrates prepared in Examples 1 to 3 were subjected to the following performance tests: ① Thermal conductivity: The thermal conductivity of the sample is measured in accordance with GB / T 32064-2015 "Test method for thermal conductivity and thermal diffusivity of building materials by transient plane heat source"; ② Dielectric loss: The dielectric loss of the sample was tested using a broadband dielectric impedance meter E4990A, where the test frequency was 10 9 Hz; The test results are shown in Table 3: Table 3 Thermal conductivity and dielectric loss test results of Examples 1 to 3
[0057] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high temperature co-fired multilayer ceramic substrate, characterized in that: The raw materials include the following components in parts by weight: 100 parts of aluminum oxide, 4-12 parts of tungsten diboride, 6-18 parts of borate compounds, 3-6 parts of sintering aids, 2-4 parts of dispersants, 5-10 parts of binders, and 50-60 parts of solvents; The borate compounds include metaborate and polyborate in a weight ratio of 1 to 9:
1.
2. The high temperature co-fired multi-layer ceramic substrate according to claim 1, characterized in that: The weight ratio of the metaborate to the polyborate is 3-7:
1.
3. The high temperature co-fired multi-layer ceramic substrate according to claim 1, characterized in that: The metaborate includes one or more of sodium metaborate, calcium metaborate, and potassium metaborate; The polyborate includes one of sodium tetraborate and potassium pentaborate.
4. The high temperature co-fired multi-layer ceramic substrate according to claim 1, characterized in that: The raw materials also include the following components in parts by weight: 2 to 8 parts of crystalline silicon dioxide.
5. The high temperature co-fired multi-layer ceramic substrate according to claim 4, characterized in that: The crystalline silica is titanium composite crystalline silica.
6. The high temperature co-fired multi-layer ceramic substrate according to claim 5, characterized in that: The raw materials of the titanium composite crystalline silica include crystalline silica and a titanium source in a weight ratio of 16:1 to 5; The titanium source includes one of acetylacetonato titanium and titanium citrate.
7. The high temperature co-fired multi-layer ceramic substrate according to claim 6, characterized in that: The preparation method of the titanium composite crystalline silica comprises the following steps: A1, adding the crystalline silica to an alkaline solution, dispersing evenly, concentrating, and drying to obtain pretreated crystalline silica; A2. Dissolve the titanium source in isopropanol, add the pretreated crystalline silica, disperse, concentrate, dry, and calcine to obtain titanium composite crystalline silica.
8. The high temperature co-fired multi-layer ceramic substrate according to claim 6, characterized in that: The weight ratio of the crystalline silica to the titanium source is 16:2-3.
9. The high temperature co-fired multi-layer ceramic substrate according to claim 1, characterized in that: The sintering aid includes one or more of Y2O3, Li2O, Cr2O3, and La2O3; The dispersant includes one or two of tributyl phosphate and triolein; The binder includes one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, and polyvinyl butyral; The solvent is water and an organic solvent, and the organic solvent includes one or more of ethanol, n-butanol, and acetone.
10. A method for preparing a high temperature co-fired multi-layer ceramic substrate, used for preparing a high temperature co-fired multi-layer ceramic substrate according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, after mixing the remaining raw materials except the solvent, dispersant and binder, adding the solvent and dispersant, performing the first ball milling, adding the binder, performing the second ball milling, and obtaining the casting slurry; S2, degassing, casting and drying the tape-casting slurry to obtain a green porcelain tape; S3, punching, filling, printing, laminating, sintering and cooling the raw ceramic tape to obtain a high-temperature co-fired multi-layer ceramic substrate.
Citation Information
Patent Citations
Chip pasting insulating adhesive with high heat conduction coefficient and preparation method of chip pasting insulating adhesive
CN110396386A
Alumina-based composite ceramic substrate and preparation method thereof
CN114656245A
Ceramic substrate and preparation method thereof
CN115286397A
Alumina ceramic plate membrane as well as preparation method and application thereof
CN116199502A
A ceramic material, reinforced by the incorporation of alumina fibers and process for production thereof
EP0468486A1
Cited By
Low dielectric constant multilayer ceramic substrate and preparation method thereof
CN120136533A
Low dielectric constant multilayer ceramic substrate and preparation method thereof
CN120136533B